FAKTOR -FAKTOR YANG MEMPENGARUHI HIPERTENSI WANITA MENOPAUSE DI PUSKESMAS TERMINAL - Dewi Iswandari, Novita; Siti Noor Hasanah (Midwifery And Complementary Care, 2023)
Background: Menopause is a natural phase experienced by women. This condition is caused by a decrease in estrogen and progesterone hormones from the ovaries, which leads to the cessation of egg release and eventually stops menstrual activity altogether. Postmenopausal women have a higher risk of hypertension compared to premenopausal women. This is due to an increased risk of atherosclerosis, which can ultimately lead to hypertension. Hypertension can damage body organs and cause stroke, kidney failure, and heart attacks. The Terminal Community Health Center ranks first among the top ten diseases with the highest number of hypertension cases. Objective: To determine the incidence of hypertension in postmenopausal women in the working area of the Terminal Community Health Center. Method: This research uses a quantitative analytic survey with a cross-sectional approach. The population consists of all postmenopausal women in the working area of the Terminal Community Health Center, totaling 156 individuals. Sampling was done using purposive sampling, with 61 respondents. Data analysis was conducted using the chi-square test. Results: The study showed that the majority of respondents experienced stage 2 hypertension, totaling 33 respondents (54.1%). A total of 42 respondents (68.9%) had a history of hormonal contraceptive use, 33 respondents (54.1%) had a normal BMI, 57 respondents (93.4%) had a primary level of education, and 40 respondents (65.6%) were employed. Statistical analysis using the chi-square test showed no relationship between a history of contraceptive use (p=0.531, p>0.05), body mass index (p=0.458, p>0.05), education (p=0.403, p>0.05), and occupation (p=0.399, p>0.05) with the incidence of hypertension in postmenopausal women in the Terminal Health Center’s working area. Conclusion: There is no relationship between contraceptive history, body mass index, education, or occupation with the incidence of hypertension in postmenopausal women in the working area of the Terminal Community Health Center. Keywords: Hypertension, Body Mass Index, Menopause, Education, Contraceptive History